The current state of the problem of drug hepatotoxicity and measures of its prevention and treatment - Shmanko, Volodymyr; Shmanko, Oleh; Lazarchuk, Tetyana (Journal of Education, Health and Sport, 2023)
Drug use is one of the most important causes of liver damage and ranks 3rd after viral diseases and alcohol. Hepatotoxicity of drugs remains one of the urgent problems of modern medicine, as it leads to a decrease in the effectiveness of pharmacotherapy, development of serious complications that can cause disability and death. Such a side effect increases the length of stay of patients in the hospital and increases the cost of treatment. That is, the problem of hepatotoxicity is not only a medical, but also a social problem. Research sources focused on modern views about drug hepatotoxicity are reviewed and summarized and new approaches to its prevention and treatment are analyzed. Conclusions. Hepatotoxicity of drugs remains one of the urgent problems of modern medicine, as it leads to a decrease in the effectiveness of pharmacotherapy, development of serious complications that can cause disability and death. Such a side effect increases the length of stay of patients in the hospital and increases the cost of treatment. That is, the problem of hepatotoxicity is not only a medical, but also a social problem.